2023
DOI: 10.3389/fped.2023.1217650
|View full text |Cite
|
Sign up to set email alerts
|

To be born twin: effects on long-term neurodevelopment of very preterm infants—a cohort study

Camilla Fontana,
Paola Schiavolin,
Giulia Ardemani
et al.

Abstract: ObjectiveTo examine the effect of twin birth on long-term neurodevelopmental outcomes in a cohort of Italian preterm infants with very low birth weight.Study designWe performed a retrospective cohort study on children born in a tertiary care centre. We included children born between 1 January 2007 and 31 December 2013 with a gestational age (GA) of ≤32 weeks and birth weight of <1,500 g. The infants born from twin pregnancies complicated by twin-to-twin transfusion syndrome and from higher-order multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…When comparing singletons to multiples there were no difference in mortality and NDI, which is similar to the results reported in an Italian study and in a recent systematic review. [19,45] In contrast to Taborda et al, who reported that monochorionic twins had an increased risk of severe neurodevelopmental delay. [20] The current results can be related to a better prenatal care with closer monitoring of twin pregnancies.…”
Section: Discussionmentioning
confidence: 93%
“…When comparing singletons to multiples there were no difference in mortality and NDI, which is similar to the results reported in an Italian study and in a recent systematic review. [19,45] In contrast to Taborda et al, who reported that monochorionic twins had an increased risk of severe neurodevelopmental delay. [20] The current results can be related to a better prenatal care with closer monitoring of twin pregnancies.…”
Section: Discussionmentioning
confidence: 93%